Phylogenetic Analysis and Molecular Characterization of Xanthium sibiricum Using DNA Barcoding, PCR-RFLP, and Specific Primers - Tomasello, Salvatore; Heubl, Günther (Planta Medica, 2017)
The fruits of Xanthium sibiricum have been widely used in traditional Chinese medicine for the treatment of nasal sinusitis and headaches. The genus Xanthium (cocklebur) is a taxonomically complex genus. Different taxonomic concepts have been proposed, some including several species, others lumping the different taxa in a few extremely polymorphic species. Due to the morphological similarities between species, the correct authentication of X. sibiricum is very difficult. Therefore, we established a polymerase chain reaction-restriction fragment length polymorphism method and diagnostic PCR based on nuclear internal transcribed spacer and chloroplast trnQ-rps16 barcodes to differentiate X. sibirium from related species.Results from the phylogenetic analyses based on sequence information from four marker regions (plastidal psbA-trnH and trnQ-rps16 and nuclear ITS and D35) support those taxonomic concepts accepting a reduced number of species, as four to five major clades are revealed in the phylogenetic reconstructions. X. sibiricum, together with some accessions from closely related taxa, is always supported as monophyletic, constituting a well-defined genetic entity. Allele-specific primer pairs for ITS and trnQ-rps16 were designed to amplify diagnostic products from the genomic DNA of X. sibiricum. Specific PCR in combination with digestion using the restriction enzyme MseI allowed for the identification of X. sibiricum by producing specific restriction patterns. The results demonstrate that the applied techniques provide effective and accurate authentication of X. sibiricum.
Keywords: Asteraceae; Xanthium; Xanthium sibiricum; phylogeny; Chinese medicine; internal transcribed spacer (ITS); PCR- RFLP